Confirmatory factor analysis of VISA-P scale and measurement invariance across sexes in athletes with patellar tendinopathy - Sergio Hernandez-Sanchez; Ferran Abat; María D. Hidalgo; Antonio I. Cuesta-Vargas; Victor Segarra; Jose M. Sanchez-Ibañez; Antonia Gomez-Conesa (Elsevier, 2017)
Background: The Victorian Institute of Sport Assessment-Patella (VISA-P) scale is the most condition-specific patient-reported outcome measure used to assess symptom severity in athletes with patellar tendinopathy. Previous exploratory factor analyses have been conducted to evaluate the scale's dimensionality, with inconsistent results, and the factor structure of the scale remains unclear. The aims of the present study were to determine the factorial structure of the VISA-P scale using confirmatory factor analysis (CFA) and test measurement invariance across sexes. Methods: The study included a convenience sample of 249 Spanish athletes with patellar tendinopathy. CFA was performed to assess factorial validity. Hypothesized 1- and 2-factor models were tested. Measurement invariance across sexes was evaluated via multi-group CFA with several fit indices using EQS 6.1 software. Results: The internal consistency coefficient was 0.74. Several CFA models were examined and the 1-factor model in which errors for Items 7 and 8 were correlated showed acceptable fit in terms of comparative fit index (CFI) and goodness-of-fit index (GFI) statistics (CFI = 0.93; GFI = 0.94; standardized root mean square residual = 0.06; root mean square error of approximation = 0.10; 90% confidence interval: 0.08-0.13). This model was invariant across sexes. Conclusion: The 1-factor model of the Spanish version of the VISA-P scale (VISA-P-Sp) in which errors for Items 7 and 8 were correlated demonstrated relative fit in CFA. Scores obtained via VISA-P-Sp can be compared between men and women without sexes bias. Further studies should examine the VISA-P scale and other single-score patient-reported outcome measures concurrently.